What Does Evaluation Look Like in a Trust-Based Context? (Trust-Based Philanthropy Project, 2023)
The fifth session of the Demystifying Trust-Based Philanthropy webinar series took place on Wednesday, July 12th 2023. There is a misperception that trust-based philanthropy is at odds with rigorous impact evaluation because of its focus on relationships over project-specific metrics. Trust-based evaluation is indeed rigorous, but it differs from the sector standard in that it prioritizes a learning stance over a proving stance. This ultimately helps illuminate a more nuanced understanding of the barriers and catalyzers of social change, as well as useful information that can help grantmakers improve their strategies toward advancing impact. This session unpacked these important nuances and highlighted examples of how grantmakers are relying on rigor and continuous learning to understand impact. Special thanks to our speakers for this session: Brenda Solorzano, CEO, Headwaters Foundation Sarah Walczyk, Executive Director, Satterberg Foundation Shari Turitz, Vice President for Programs, American Jewish World Service Gratitude to our philanthropic-serving organization partners for bringing this session and discussion space to their grantmaker members. Learn more about the Trust-Based Philanthropy Project: Website: https://www.trustbasedphilanthropy.org/ Follow us on Twitter: / trustbasedphil Follow us on LinkedIn: / trust-based-philanthropy